Effects of the association between Mimus saturninus and Furnarius rufus on their foraging and alert behaviors - Piassi, Priscila M. [UNESP]; Batisteli, Augusto F.; Gussoni, Carlos O. A.; Pizo, Marco A. [UNESP] (Springer Nature, 2022)
Several studies on the social behavior of birds have shown two main benefits of social groups: optimization of foraging and decreasing the risk of predation. We tested whether the association between rufous hornero (Furnarius rufus) and the chalk-browed mockingbird (Mimus saturninus) affects the foraging and alert/sentinel behaviors of both species. We also evaluated the influence of group size on these behaviors. During 60 h of observations on each species, the association was studied in a periurban area in Brazil with scan samplings. The presence of F. rufus increased the frequency of foraging while reducing the time that M. saturninus dedicated to alert/sentinel behaviors. For F. rufus, however, the presence of M. saturninus did not affect the studied behaviors, although a different study pointed out that this species could also benefit from the association with M. saturninus, indicating that both species may occasionally be positively affected by the association with each other.
Keywords: Foraging behavior; Grouping effects; Heterospecific group; Sentinel behavior; Urban birds